2016
DOI: 10.1136/archdischild-2016-310632
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-minute consultation: enterovirus meningitis and encephalitis—when can we stop the antibiotics?

Abstract: Enterovirus (EV) is the most common cause of aseptic meningitis and has a benign course, unlike EV encephalitis, which can result in long-term neurological sequelae. There are no active treatments or prophylactic agents, and management is purely supportive. Obtaining an EV-positive cerebrospinal fluid result usually allows antimicrobial treatment to be stopped. This review will answer some of the common questions surrounding EV meningitis/encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…All children without concomitant bacterial infection underwent antibiotic therapy that lasted 5 or more days in approximately 2/3 of cases. C-reactive protein levels increased in only a few cases and could not account for the prolonged antibiotic treatments, since more recent literature suggests discontinuing therapy when EV infection is confirmed [33].…”
Section: Discussionmentioning
confidence: 99%
“…All children without concomitant bacterial infection underwent antibiotic therapy that lasted 5 or more days in approximately 2/3 of cases. C-reactive protein levels increased in only a few cases and could not account for the prolonged antibiotic treatments, since more recent literature suggests discontinuing therapy when EV infection is confirmed [33].…”
Section: Discussionmentioning
confidence: 99%
“…A positive diagnosis of HPeV infection would allow cessation of antibiotic therapy and may thereby facilitate earlier discharge from hospital (86). In addition, testing HPeV using PCR in blood samples of infants who are being evaluated for infection would increase the diagnostic yield as higher viral loads are seen in serum compared with CSF (51).…”
Section: Improving Diagnosis Of Parechovirus Infectionsmentioning
confidence: 99%
“…At present clinical guidelines do not differentiate between the management of children presenting with EV versus HPeV infections. 3 This study demonstrates that differences in the severity of clinical illness can be seen between the HPeV and EV CNS infections, with a greater degree of severity in HPeV cases. Further studies are required to clarify and confirm these findings, which may then lead to more practical clinical guidelines for the immediate and longer-term management and followup of these patients.…”
Section: Discussionmentioning
confidence: 65%
“…Although some previous studies have found pediatric HPeV and EV infections clinically indistinguishable, 1,3 anecdotally, in our pediatric population, nurses who worked with children involved in our recent HPeV outbreak, 2 reported that they were able to distinguish which children had HPeV rather than EV, prior to any laboratory confirmation, on their clinical presentation alone. These HPeV cases were noted to be generally more irritable and persistently unconsolable, tachychardic and pyrexial than the more frequently encountered annual, seasonal EV cases with which the nurses were very familiar.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation